Atrial Tachycardia Revealing Obstructive Left Atrial Myxoma. Case Report - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2024)
Myxomas are the most common primary cardiac tumors; the most common localization is the left atrium, and may cause mitral flow obstruction so their clinical presentation could mimic severe mitral stenosis; trans thoracic echocardiography allows the diagnosis; we report a case of left atrial myxoma revealed by atrial tachycardia concomitant with dyspnea and signs of chronic right heart failure; despite surgical resection of the tumor, our patient had developed tachycardiomyopathy with severe left ventricular dysfunction, which recovered two months later, after intensive administration of antiarrhythmic treatment.